PERBEDAAN KEMANDIRIAN BELAJAR SISWA ANTARA PEMBELAJARAN BERBASIS MASALAH DENGAN PENEMUAN TERBIMBING - Riskyka (LPPM STKIP AL MAKSUM, 2020)
This research aims to know: (1) the differences of self-regulated learning between students who taught problem-based learning with guided discovery, (2) the interaction between the learning model and the initial ability of mathematics towards self-regulated learning. This research is a quasi-experimental research. The research population was eighth grade junior high school students of SMP Negeri 5 Stabat, then have two classes of ninth grade. The instrument used self-regulated learning scale. Data analysis is used by analysis of variance (ANOVA) two lines. The results showed that (1) there are differences of self-regulated learning between the students who taught problem-based learning with guided discovery, where the application of problem based learning model is better than students who received learning guided discovery to self-regulated learning (2) there is no interaction between the learning model and initial ability of mathematics towards self-regulated learning. This shows that the contribution of jointly given by learning model with the initial ability of mathematics students do not have a significant effect on the development of students‘s self-regulated learning.